FAKTOR-FAKTOR YANG MEMPENGARUHI FUTURE EARNINGS RESPONSE COEFFICIENT PADA PERBANKAN ASEAN - Gabby Naca Stevany; Elsa Imelda (Jurnal Paradigma Akuntansi, 2026)
The goal of this research is to determine how corporate social responsibility, company size, company growth, earnings persistence, and earnings volatility affect the future earnings response coefficient on banking in 5 ASEAN countries from 2018 to 2020. The sample used 102 banks as samples selected for purposeful sampling. The data is then examined using multiple linear regression analysis using the program EViews (Econometric Views) version 12. The results of this research indicate that corporate social responsibility has a significant positif effect on future earnings response coefficient and earnings persistence have a significant negative effect on future earnings response coefficient.